Pengetahuan Produk dan Dampaknya terhadap Perilaku Mencari Variasi - Tjiptodjojo, Kartika Imasari (Zenit, 2015)
Basically, consumers have a level of product knowledge that can be used in decision making and behavior. Knowledge of consumer products is divided into tiers, from the most abstract to themost concrete. Consumers who have high knowledge about a particular product usually have complete information about a product that will make it easier for them to seek a variation of theproduct. This study used 100 samples with the criteria for the use and purchase of mobile phones (Smartphones or Tablets) Samsungâs brand.Keywords: Product knowledge, Variety Seeking Behavior, mobile phones